Optimization of direct conversion of methane to liquid fuels over Cu loaded W/ZSM-5 catalyst - Saidina Amin, Nor Aishah (Elsevier BV, 2004)
The optimization of methane conversion to liquid fuels over copper loaded W/ZSM-5 catalyst was studied by utilizing experimental design from 'Statsoft Statistica' version 6.0 software. Response surface methodology was employed to determine the optimum methane conversion and C5+ selectivity. Numerical results indicated the optimum methane conversion of 29. 4% with the corresponding C5+ selectivity of 57.2% were achieved at 12.3vol% of O2, 203.9 ml/min of total feed flow rate, and %W doped of 3.2wt%. The optimum C5+ selectivity of 70.2% was attained at 7.6vol% of O2, 208.9 ml/min of total feed flow rate, and 3.2wt% of W content with the corresponding methane conversion of 26.7%. By means of variance analysis and additional experiments, the adequacy of this model is confirmed.